The Competitiveness of Global Coffee Trade - Torok, Aron; Mizik, Tamas; Jambor, Attila (International Journal of Economics and Financial Issues, 2018)
Coffee is an important agricultural raw material and part of international trade. Although global production is extremely concentrated, it is mainly sold to developed markets. The aim of the paper is to analyse the comparative advantages of the biggest producers. Results suggest that coffee trade has increased recently with important changes in the key players. Brazil, Vietnam and Colombia are currently the biggest exporters, giving the majority of global trade. However, Balassa indices were the highest for Uganda, Ethiopia and Honduras, suggesting unreasonable specialisation patterns. Furthermore, stability and duration tests show significantly changing trends, implying fierce competition in these markets. Keywords: coffee trade, revealed comparative advantages, competitiveness JEL Classifications: Q17, Q13 https://doi.org/10.32479/ijefi.6692